Effect of China's energy conservation efforts on reducing health damage. (February 2019) - Yang, Xi; Xi, Xiaoqian; Lin, Wanqi; Guo, Shan
Abstract: The paper considers the health damage effect attributed to energy consumption and local pollutant emissions, which has been long ignored because of cost. The study bases on national level and conducts a four-scenario analysis, including Reference Scenario (REF), Deep Decarbonization Pathway Scenario (DDP), End-of-Pipe Control Scenario (EPC), and Co-Control Scenario (COC). By applying China-MAPLE model and CV method, the study calculates the future emissions of air pollutants in China and its health damage. Results show that in COC scenario, the emissions of SO2, NOX and PM2.5 will drop to 1.76, 8.43 and 6.43 million tons respectively in 2030, and the economic losses caused by PM-SO2, PM-NOX and PM2.5 emissions are 0.159 %, 0.025% and 1.604% of China's 2010 GDP respectively, and in 2050, the proportions drop to 0.098%, 0.014% and 1.128%. The results provide a reference for the government to formulate policy.